The Effect of Digital Banking Adoption and Fintech Competition on The Profitability of Conventional Commercial Banks in Indonesia - Indah Berutu; Tuti Meutia; Agustina Nurul Fajriah (Asosiasi Dosen Akuntansi Indonesia, 2026)
This study aims to examine the effect of digital banking adoption and fintech competition on the profitability of conventional commercial banks in Indonesia. The rapid growth of financial technology has prompted banks to accelerate their digital transformation amid increasing competitive pressure from fintech firms. This study uses a quantitative method with an associative-causal approach. The data used is secondary data from the financial statements of banks listed on the Indonesia Stock Exchange for the 2019–2024 period. The sample comprises 8 banking companies selected through purposive sampling based on predetermined criteria aligned with the study's objectives. Data analysis was carried out using multiple linear regression. The results show that the adoption of digital banking had a positive effect on profitability (p=0.019), while fintech competition had a significant negative effect (p=0.017). Simultaneously, the two variables had a significant effect on bank profitability, with a value of 0.013. This study shows that increasing digitalization can improve banks' financial performance, but competition from fintech is a challenge that the banking industry needs to anticipate.